FOOD SECURITY: PROBLEMS AND PROSPECTS IN RUSSIA - Ivan Mikhailovich KULIKOV; Ivan Alekseevich MINAKOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The population-genetic analysis wascarried outby ISSR-PCR markers of animals of the local Lebedyn breed and breeds that participated in its formation and improvement: Swiss, Ukrainian Grey and original Brown Swiss. ISSRPCR technology showed a low level of genetic heterogeneity in all animals of investigated breeds having unique species-specific DNA fragments. The low levels of genetic polymorphy and heterozygosity, particularly in the subpopulation of Lebedyn breed animals, give evidence to the presence of genetic erosion and the threat of inbred depression. The results of evaluation of genetic differentiation between breed founders and based on them Lebedyn breed were proved to be used in the breeding programs for its gene pool restoration. Taking into account the results of population-genetic analysis, a fundamentally new scheme of reproduction of the genealogical structure of aboriginal breeds by the reciprocal population reproduction method was developed.